The Relationship between capital adequacy and profitability under Basel III in the Namibian banking sector - Pomuti, Esther Kaulinawa (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
Globally, capital adequacy is one of the most central topics for both regulatory authorities and banks. It promotes stability and intends to reduce bank insolvency. It also represents the most important element of banks' profitability (Profits are the first line of defense against losses from credit loss in a bank). After the collapse of Bretton Woods in 1973, many banks incurred large foreign currency losses, with Banks outside Germany having taken heavy losses on their unsettled trades with Herstatt Bank in Cologne, West Germany, when it collapsed in June 1974. This study empirically tests the relationship between changes in the capital adequacy ratio under Basel III and return on equity (ROE) of the Namibian banking sector and whether such relationships exist in the short run or long run. The study used panel quarterly data for a sample of three Namibian commercial banks from the year 1999 to 2019.It employed one panel unit root tests namely: Im, Pesaran and Shin W-stat (IPS). To test the existence of a long-run relationship (equilibrium) or effect between the dependent and independent variables, the study employed the Panel Co-integration methods using Pedroni and Kao (Engle-Granger based) tests. The study carried out the Hausman test to determine the best approach for analysis and determined the PMG approach to be the preferable model for analysis. Various diagnostic tests such as multicollinearity through the correlation analysis, autocorrelation, and heteroscedasticity and cross-sectional dependence tests were carried out to determine if the data set is well-modelled and if the results can be taken seriously. The study's results under the PMG model showed that ROE and CAR have a positive significant relationship in the short run. A dummy variable to capture the connection between ROE and CAR before and after BASEL III shows that the relationship is positive and significant indicating that ROE increases more when there is capital regulation than when there is no capital regulation. The study also concluded that there is no long run relationship between CAR and ROE. Finally, the interaction effect between the dummy variable and CAR is negative but significant and thus indicating that the positive relationship does not persist post Basel III.
Keywords: Banks and banking-- Namibia; Banks and banking, International Law and legislation; Bank capital Law and legislation-- Namibia; Rate of return-- Namibia; Basle Committee on Banking Supervision; Ratio analysis; Basel III (2010)